Some Recent Systems Development by U.S. Coast and Geodetic Survey - Hickley, Thomas J. (The International Hydrographic Review, 2015)
Systems Development plays a major part in the research and development programs of the U.S. Coast and Geodetic Survey. The general purpose of this phase of research and development is not only to develop new means of collecting data at sea and on land, but to collect oceanographic and geophysical data more efficiently, and to process these data more rapidly. Another purpose, equally important, is to develop higher quality in instrumentation measurements through calibration and standardization. Of the systems thus far developed by the Coast and Geodetic Survey that shall be discussed, all are beyond the planning stage and have been laboratory and field tested; some are in the test and evaluation stages; and in such cases where redesign is indicated, the program has not been completed.